The Impact of Accounting Information Quality on Enterprise Technology Innovation - Sun, Yuxin (2019)
In the past decade, the impact of the quality of accounting information on corporate investment has attracted the attention of scholars. However, the current related research mainly discusses the impact of the quality of accounting information on overall investment, but less considers the impact of the quality of accounting information on specific investment projects. The technological innovation of enterprises is a special and important investment, which is of great significance to the construction of the core competitiveness of enterprises and the development of macroeconomics. Therefore, it is necessary to specifically study the impact of the quality of accounting information on the technological innovation of enterprises. In view of this, this dissertation will use the sample of 2320 listed companies in China from 2016 to 2018 to explore the impact of the quality of accounting information on the value of technological innovation. The study will find that the quality of accounting information is significantly positively correlated with the level of investment in technological innovation of enterprises, that is, improving the quality of accounting information is conducive to promoting the investment in technological innovation.